Prinsip Oikumenis dan Keadilan Sosial: Analisis Berdasarkan Kitab Mikha 6:8 - Siregar, Esron Mangatas; Rangkang , Oktapianus; Agus , Afriatus (ICHTUS: Jurnal Teologi dan Pendidikan Kristiani, 2025)
This article explores the close relationship between ecumenical principles and social justice based on the teachings of Micah 6:8. In Indonesia’s diverse context, issues such as religious discrimination, legal injustice, social inequality, and abuse of power are significant barriers to achieving a just and prosperous society. Using a descriptive and literature-based approach, this study examines God’s demands on His people—to act justly, love faithfulness, and walk humbly with Him. These three values serve as the moral and spiritual foundation for building a society grounded in justice and equality. The prophet Micah emphasizes that God is the source of true justice and calls His people to embody this character in everyday life. The ecumenical movement is seen as a strategic means of uniting Christians across denominations to advocate for social justice, peace, and collective well-being. The article asserts that social justice is not merely a moral responsibility but a divine calling that must be realized collectively by all segments of society. By adopting the values taught in the Book of Micah, churches and believers can serve as agents of transformation, working toward a socially just and harmonious society in accordance with God's will.   Artikel ini mengkaji hubungan erat antara prinsip oikumenis dan keadilan sosial berdasarkan ajaran kitab Mikha 6:8. Dalam konteks Indonesia yang majemuk, diskriminasi agama, ketidakadilan hukum, ketimpangan sosial, dan penyalahgunaan kekuasaan menjadi tantangan nyata yang menghambat terwujudnya masyarakat adil dan sejahtera. Penelitian ini menggunakan pendekatan deskriptif dan kajian literatur untuk menggali makna tuntutan Tuhan terhadap umat-Nya, yakni berlaku adil, mencintai kesetiaan, dan hidup dengan rendah hati. Tiga nilai ini menjadi fondasi moral dan spiritual dalam membangun masyarakat yang menjunjung keadilan dan kesetaraan. Mikha menegaskan bahwa Allah adalah sumber keadilan sejati, dan umat dipanggil untuk mencerminkan karakter tersebut dalam kehidupan sehari-hari. Gerakan oikumenis dipandang sebagai sarana strategis untuk menyatukan umat Kristen lintas denominasi dalam memperjuangkan keadilan sosial, perdamaian, dan kesejahteraan bersama. Artikel ini menegaskan bahwa keadilan sosial bukan sekadar tanggung jawab moral, tetapi panggilan ilahi yang harus diwujudkan secara kolektif oleh seluruh lapisan masyarakat. Dengan menjadikan nilai-nilai kitab Mikha sebagai panduan, gereja dan umat beriman dapat menjadi agen perubahan dalam menciptakan tatanan sosial yang adil dan harmonis.